Risk Factors Influencing the Occurrence of Urinary Tract Infections in Inpatients - Ardiana Ardiana; Syah Mirsya Warli; Kiking Ritarwan; R. Lia Kusumawati; Juliandi Harahap (GLOBAL HEALTH SCIENCE GROUP, 2024)
A urinary tract infection is an infection of the urinary tract both upper and or lower, where the number of bacteria is greater than 10⁵ bacterial colonies per unit per ml in a urine specimen. Several studies have shown that there are risk factors that can cause urinary tract infections such as age, gender, long lying down, and other predisposing factors. Objective: To identify the factors that influence the occurrence of urinary tract infections in H. Adam Malik Hospital Medan. Method: This study was designed cross-sectional approach. 59 patients were applied in this study using consecutive sampling. Data were collected using a questionnaire and analyzed using chi-square and Fisher. Results: the results showed that there was no relationship (p>0.05) among age (p=0.869; OR=0.9), gender (p=0.812; OR=1.1), predisposing factors with diabetes mellitus (p=0.146), human immunodeficiency virus (p=0,286), kidney disease (p=0,386), autoimmune (p=0,641) and there were significant relationship (p< 0.05) among prolonged lying down (p=0.04; OR=3,1) were the most significant factor related to urinary tract infection without urinary catheter. Conclusions: the results showed that there was no relationship among age, gender, or predisposing factors such as diabetes mellitus, human immunodeficiency virus, kidney disease, or autoimmune disease with the incidence of urinary tract infection. Long lying down is a relationship with urinary tract infection.